THE MORPHOLOGY, SYSTEMATICS AND PALEOECOLOGY OF THE LYCOPSID VIATCHESLAVIA VORCUTENSIS - Naugolnykh S.V. (My University, 2001)
The lycopsid Viatcheslavia vorcutensis is regarded as a stratigraphically valuable index fossil for the Lower Ufimian deposits of Western Angaraland. The morphology of V. vorcutensis is considered. Sporophylls of the species are described for the first time. A new interpretation of certain morphological features is suggested, and the ecology of the species is discussed.